Correlation of Premature Infant Sleep/ Wakefulness and Noise Levels in the Presence or Absence of Quiet Time - Pugliesi, Raiani Roberta; Campillos, Michelle Siqueira; Sbampato Calado Orsi, Kelly Cristina; Avena, Marta Jose; Cacia Pradella-Hallinan, Marcia Lurdes de; Tsunemi, Miriam Harumi [UNESP]; Machado Avelar, Ariane Ferreira; Pinheiro, Eliana Moreira (Lippincott Williams & Wilkins, 2018)
Background: Peak sound levels during sleep can compromise the development of hospitalized infants. Quiet time is a strategy implemented in neonatal units to promote the sleeping of neonates by reducing noise levels, luminosity, and handling during particular periods of the day. Purpose: To determine the impact of quiet time on reducing sound levels and increasing total sleep time. Methods: This longitudinal study was conducted at a neonatal intermediate care unit with a convenience sample of 12 premature infants. Four times per day, 60 minute quiet times were provided in the neonatal unit. Sleep-awake states and sound levels were evaluated during quiet times as well as 60 minutes before and afterward. Polysomnography was used for sleep-awake state assessment, and a noise dosimeter was used to check sound levels every 24 hours. Results: The preterm infants had a corrected gestational age of 35.0 +/- 1.5 weeks and weighed 1606.0 +/- 317.8 g. Total sleep time was highest during quiet time (P = .005). Premature infants remained awake for longer following quiet times (P = .005). There was also a reduction in sound level during quiet times compared with the other time frames (P = .006). No statistically significant relationship was found between total sleep time and sound levels more than 24 hours Implications for Practice: Quiet time is a nursing intervention that should be implemented in all neonatal units. Implications for Research: Future research should use a greater sample size and other factors that influence sleep should be further investigated.
Keywords: neonatal nursing; noise; nursing care; polysomnography; premature infant; sleep